On the epistolary as a function of eros in Aidan Higgins's Bornholm Night-Ferry. Issue 12 (2nd December 2021) - Lee, Cheryl Julia
ABSTRACT: Anne Carson argues in eros: The Bittersweet that insofar as eros is lack, it requires three components to be 'activated': 'lover, beloved and that which comes between them' (16); and the activity of eros consists in reaching across that-which-comes-between-them. For Carson, it is writing above all utterances that most evidently manifests this structure of desire – as Aidan Higgins's 1983 novel, Bornholm Night-Ferry, demonstrates. The novel tells the love story of two people who are held apart by every possible circumstance and who yet reach across the amorous impasse for each other by way of letters. In telling this exemplary story of eros as reach, Higgins aptly challenges and extrapolates the conventions of the epistolary mode beyond its function as a testament to reality. The result of his experimentations is the revelation of the epistolary as an imaginative and dynamic mode that participates in the forging of reality – a revelation that challenges the Barthesian assertion that writing is always inadequate to the task of expressing reality.